Photofunctionality in Porphyrin‐Hybridized Bis(dipyrrinato)zinc(II) Complex Micro‐ and Nanosheets. (27th February 2017) - Sakamoto, Ryota; Yagi, Toshiki; Hoshiko, Ken; Kusaka, Shinpei; Matsuoka, Ryota; Maeda, Hiroaki; Liu, Zheng; Liu, Qian; Wong, Wai‐Yeung; Nishihara, Hiroshi
Abstract: New bis(dipyrrinato)zinc(II) complex micro‐ and nanosheets containing zinc(II) porphyrin (N2 ) are synthesized. A liquid/liquid interface method between dipyrrin porphyrin ligand L2 and zinc acetate produces N2 with a large domain size. N2 can be layered quantitatively onto a flat substrate by a modified Langmuir–Schäfer method. N2 deposited on a SnO2 electrode functions as a photoanode for a photoelectric conversion system. The photoresponse of N2 covers the whole visible wavelength range (400–650 nm), with a maximum quantum efficiency of more than twice that of a bis(dipyrrinato)zinc(II) complex nanosheet without porphyrin. Abstract : Lichtschicht : Eine Synthese an der Flüssig‐flüssig‐Grenzfläche liefert Mikro‐ oder Nanoschichten aus einem Bis(dipyrrinato)zink(II)‐Komplex. Porphyrinhaltige Nanoschichten wurden auf eine SnO2 ‐Elektrode übertragen, um eine Photoanode zu erzeugen, die das gesamte sichtbare Spektrum (400–650 nm) abdeckt. So wird eine höhere maximale Quanteneffizienz erreicht als mit porphyrinfreien Nanoschichten.